(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The body has death, but not the soul. The body sleeps, the soul flies. The soul-stirring words on death and the soul in this chapter of the Gita, let us recollect. “Even as man discards old clothes for the new ones, so the dweller in the body, the soul, leaving aside the worn-out bodies, enters into new bodies. The soul migrates from body to body. Weapons cannot cleave it, nor fire consume it, nor water drench it, nor wind dry it.” This is the soul and this is what is meant by the existence of the soul.